ChemInform Abstract: Synthesis, Structural Characterization and High Pressure Phase Transitions of Monolithium Hydronium Sulfate. Issue 7 (22nd February 2013) - Banerjee, Debasis; Plonka, Anna M.; Kim, Sun Jin; Xu, Wenqian; Parise, John B.
Abstract (H3O)LiSO4 is solvothermally synthesized from a mixture of LiNO3, 1, 5‐naphthalenedisulfonic acid tetrahydrate, and NH4F dissolved in DMF (autoclave, 100 °C, 4 d, 50% yield).